2011
DOI: 10.1309/ajcphh1b0cocbgom
|View full text |Cite
|
Sign up to set email alerts
|

Formaldehyde Substitute Fixatives

Abstract: Because formaldehyde is toxic and creates cross-links that may hinder immunohistochemical studies, we tested 3 new cross-linking (F-Solv [Adamas, Rhenen, the Netherlands]) and non-cross-linking (FineFIX [Milestone, Bergamo, Italy] and RCL2 [Alphelys, Plaisir, France]) alcohol-based fixatives for routine staining in comparison with neutral buffered formalin (NBF) as the "gold standard." Fresh tissue samples were divided into 4 equal pieces and fixed in all fixatives for varying times. After paraffin embedding, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(32 citation statements)
references
References 24 publications
(25 reference statements)
0
29
1
Order By: Relevance
“…Color and consistence are evident at a glance, while other features such as shrinkage and surface modifications are more subtle. In disagreement with a recent paper [39] that reported some difficulties in handling and sectioning of samples fixed in RCL2, we did not encounter any problems in these preparative aspects. The embedding process that follows fixation may largely modify the physical qualities of samples to be included in paraffin, and influence the ease in sectioning.…”
Section: Resultscontrasting
confidence: 99%
“…Color and consistence are evident at a glance, while other features such as shrinkage and surface modifications are more subtle. In disagreement with a recent paper [39] that reported some difficulties in handling and sectioning of samples fixed in RCL2, we did not encounter any problems in these preparative aspects. The embedding process that follows fixation may largely modify the physical qualities of samples to be included in paraffin, and influence the ease in sectioning.…”
Section: Resultscontrasting
confidence: 99%
“…Kap et al report an increase in intensity of goblet cell staining in PAS of intestinal samples in Paxgene-fixed samples [26]. Similarly, Moelans et al reported that while FineFix, RCL2 and F-Solv gave adequate staining for PAS, PASD, Alcian Blue and a number of others, fixation in NBF and standard pre-optimised techniques were superior [27].…”
Section: Effect Of Molecular Fixatives On Downstream Processesmentioning
confidence: 97%
“…Moreover, SurePath contains a low concentration of formaldehyde added to the alcohol fixative to ensure adequate preservation of the cell material whereas ThinPrep uses methanol as the sole fixative. The difference in fixative has been a source of discussions internationally, with the claim that HPV analysis on SurePath samples can be challenged by the cross-linking between DNA and proteins driven by the formaldehyde content (42,43).…”
Section: Discussionmentioning
confidence: 99%